CRYPTOCURRENCY DALAM KACA MATA HUKUM ISLAM DAN HUKUM NEGARA INDONESIA - Mabrur, Imam (Islamijah: Journal of Islamic Social Sciences, 2023)
In The digital era, cryptocurrency is one of the innovations created from human dissatisfaction with the existing financial system, thus giving birth to a digital currency that has the same function as other currencies, but does not have a physical form like currency in general, but in the form of a digital currency data blocks, and is able to document transactions directly without the help of third parties through a network called Blockchain. Although it is considered a substitute for future digital currencies and provides many benefits to its users, the regulation and legality of cryptocurrencies are still questioned, especially in Islamic economic principles. This study aims to find out more about the description, regulation and legality of cryptocurrencies in Indonesia and what the perspective of cryptocurrency in Islamic financial principles. The research model used is library research, by collecting data in the form of journals, books, websites, and other objects that are considered relevant and then carried out an in-depth study through descriptive qualitative analysis methods.